Application Waste Sawdust as Mixed Polyurethane Insulation in Traditional Cold Storage of Fishing Vessel - Sutopo Purwono Fitri; Muhammad Badruz Zaman; Dwi Priyanta; Mochamad Hidayat (Department of Marine Engineering, Institut Teknologi Sepuluh Nopember, 2017)
In the process of fishing it takes some supplies such as fishing equipment, instrumentation and storage of fish. The traditional fishermen of their fishing days fishing usually only bring ice cubes. Solid plastic polyurethane foam is a mixture solution of polyols and isocyanates, commonly used as an insulating material storage. From the observation waste generated being sawmill sawdust per spindle with diameter of 30 cm and a length of 1 m with 5 times sawmill, Saws 0.8 cm thick produced 0.0088 m³ / burnable logs only discarded. Therefore takes thermal conductivity test to review mixture of sawdust and polyurethane comparison with variations different dosing. Maximum disposals sawdust can be done is 40% of the total volume of material mixture, polyurethane and sawdust because composite material (sawdust-polyurethane) can not be bond with good so easy slab separately from origin form. Thermal Conductivity insulating good and economical on disposals 40% wood flour (0.05252 W / m°C) and is able to maintain a 2 kg of ice crystals melt up perfect on 34 hours. Operating profits economical from 4,8 m³insulation composite application with obtained Rp 4.486.000 compared with 100% Polyurethane Insulation Manufacture.